1983
DOI: 10.1111/j.1471-4159.1983.tb00827.x
|View full text |Cite
|
Sign up to set email alerts
|

[3H]Imipramine Labels Sites on Brain Astroglial Cells Not Related to Serotonin Uptake

Abstract: Brain astroglial cells, whether from a bulk isolated preparation or in culture, have been shown to take up serotonin actively. [3H]imipramine has been proposed as a specific label for serotonin uptake sites in brain. We therefore studied the binding of [3H]imipramine to C6 astroglial cells in culture to determine if some of the binding of this radioligand in brain homogenates is actually to serotonin transporting sites on glia. [3H]Imipramine binds saturably (Bmax = 202 fmol/mg protein) and with high affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…This system is characterized by ligand specificity, Na+ and temperature dependence, antagonizability by known blockers (nortriptyline, imipramine, and desipramine), and saturable and high-affinity uptake kinetics. In particular, the Km and Vma values are well within the range of such parameters measured for 5-HT-uptake systems in the central nervous system and blood platelets (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This system is characterized by ligand specificity, Na+ and temperature dependence, antagonizability by known blockers (nortriptyline, imipramine, and desipramine), and saturable and high-affinity uptake kinetics. In particular, the Km and Vma values are well within the range of such parameters measured for 5-HT-uptake systems in the central nervous system and blood platelets (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 66%
“…Although the physiology and pharmacology of a number of neurotransmitter transport systems including that for serotonin have been extensively studied (6)(7)(8)(9)(10)(11)(12)(13), little is known about the biochemistry and molecular biology of any of these systems. With the hope of attaining such information, we report here the use of gene transfer (14)(15)(16)(17) in the establishment and identification of a clonal mouse fibroblast cell line, L-S1, that stably expresses a presumptively human highaffinity uptake system for serotonin (5-HT).…”
mentioning
confidence: 99%
“…A strong accumulation of GABA has already been demonstrated in cultured normal astrocytes of brain cortex of newborn mice, and a quantitative correlation between GABA and sodium transport has been established . Uptake of 5-HT by glial cells has also been reported and a Na+-sensitive component of this influx has been shown (Katz and Kimelberg 1985;Suddith et al, 1978;Whittaker et al, 1983). Similarly, glial uptake of NA has also been demonstrated (Kimelberg and Pelton 1983;Kimelberg, 1986;Pelton et al, 1981) but its saturability and Na+ dependency has been questioned (Hansson, 1985;Hertz and Peterson, 1988).…”
Section: Discussionmentioning
confidence: 96%
“…Reith et al (1983) demonstrated that the highaffinity binding of [3H]imipramine is related to the neuronal uptake system for 5-HT but inhibition of the low-affinity binding did not correlate with the inhibition of the neuronal uptake of 5-HT. Whitaker et al (1983) suggested that part of the [3H]imipramine binding occurs on astroglial cells and is not related to 5-HT transport. It is possible that the low-affinity, sodium-independent site in different brain regions could be the glial cell site.…”
Section: Discussionmentioning
confidence: 99%